Strategy for Increasing Inclusive Business of Oil Palm Small Farmers in Sijunjung Regency - Anas, Winnie Pratiwi; Mulyati, Heti; Slamet, Alim Setiawan (Jurnal Manajemen, 2023)
West Sumatra is one province that is growing its oil palm planting potential. Sijunjung Regency is one of West Sumatra's oil palm plantation hubs and home to several small farmers. Smallholder oil palm farms operated by smallholders have not been able to deliver optimum benefits and are still far behind other plantations, which renders their business exclusive. The lack of smallholder participation in the value chain is a barrier to creating an inclusive business. The purpose of this study was to develop a strategy to expand the inclusive business of smallholder oil palm producers in Sijunjung Regency. This study used the Analytical Hierarchy Process (AHP) to discover the most effective farming practices. Smallholder Assistance including Good Agriculture Practices (GAP) and Managerial is the most important strategy in this study, followed by ease of access to finance.